The Influence of Motivation for Sharing GenZ Islamic Content on Social Media - Armiah, Armiah; Falikhah, Nur; Amaly, Najla (UPT Publikasi Ilmiah UNISBA, 2023)
UIN Antasari students like and post Islamic websites through announcements of religious assemblies, videos of religious lectures, and motivational sentences, and are even active as volunteers for Islamic media such as Aswaja Net and Al Jami. The behavior of sharing Islamic content becomes interesting when it is associated with their motivational background in sharing content with others. The initial hypothesis is that there is a desire to invite others to do good, provide assistance, support each other, and prevent reprehensible actions. This study uses a mix method approach. The data collection technique is by distributing google form questionnaires and FGDs. Data analysis technique was performed by multiple linear regression analysis. The results of the study based on a sample of 566 students found that motivation and intensity simultaneously influence the behavior of sharing Islamic content. The effect value of the independent variable on the dependent variable is 58.5%. The motivation for sharing Islamic content includes selfactualization motivation in preaching as much as 75.6% and to get responses from other people as much as 72.4%. Meanwhile, the intensity of accessing Islamic content was 45.9% 2-5 times per day and 41.3% less than 10 minutes.